Does the Use of Nitroglycerin Patch Improve Local Anaesthetic Effects in Bier’s Block? A Double-Blind Placebo Controlled Study - Ahmed Said Elgebaly (Anesthesiology Research and Practice)
Aim. The aim of the study was to assess the nitroglycerin patch as a new additive to Bier’s block and its impact on the effects and dose of lidocaine. Methods. Forty patients of each sex belonging to ASA I or II underwent elective tendon repair surgeries of the forearm and hand. The patients were divided into two equal groups as follows: Group C received only lidocaine (1.5 mg/kg, 0.25%) and Group N received lidocaine (1.5 mg/kg, 0.25%) + 5 mg transcutaneous nitroglycerin patch. Onset and recovery times for sensory and motor block, visual analogue scale (VAS) scores for bandage pain, postoperative VAS score, analgesic requirements, patients’ satisfaction, and surgeons’ opinion were recorded. Results. Sensory block onset time was shorter in Group N (3.80 ± 1.0) than that in Group C (5.72 ± 1.46), and motor block onset time was shorter in Group N (10.72 ± 1.93) than that in Group C (13.56 ± 1.26). Sensory block recovery time was prolonged in Group N (10.56 ± 1.12) than Group C (6.88 ± 1.45), recovery time of motor block was prolonged in Group N (13.04 ± 1.57) than Group C (11.96 ± 1.72). Bandage pain had lower VAS scores in Group N. Postoperative VAS scores showed significant differences between both groups at the following points of measurement: 30 minutes, 1 hour, and 4 hours after bandage deflation. Postoperative analgesic effect was the longest in Group N (187.20 ± 60.79 min) than Group C (51.60 ± 25.28 min). Patients’ satisfaction and surgeons’ opinion were better in Group N than Group C. Conclusion. Supplementation of Bier’s block with transcutaneous nitroglycerin patch reduces the lidocaine dose, the sensory and motor block onset times, VAS scores, and analgesic consumption intra- and postoperatively. Length of the block recovery times for the sensory and motor effects, duration of postoperative analgesic effect, and the first time to analgesic requirement improved the quality of Bier’s block with better patients’ satisfaction and surgeons’ opinion and had no adverse effects.